CARTOGRAFIAS DA DIFERENÇA: CAUSOS DE LOUCOS NO TRABALHO, O ASSUJEITAMENTO DE PESSOAS EM SOFRIMENTO MENTAL NO MUNDO DO TRABALHO - Fabiana Florio Domingues (2021)
The objective of this thesis is to cartographier the extent to which the understanding of madness seen as disabling for formal work affects the lives of people in psychological distress in the world of work, highlighting its social, moral and ethical consequences. The biggest discomfort that we seek to answer is the qualification of the human as useful or useless for formal work, since we understand that conceiving a possible way of life in madness is accepting that there are distinct and possible worlds beyond prejudice and discrimination. Thus, we understand madness as a social construction that varies in time and space of its production, so we defend the thesis that although hegemonic discourses on madness present it as disabling, madness is just another manifestation of human differences. We base our initial proposition on the philosophy of difference, present in the work of Gilles Deleuze and Félix Guattari, including it as a possibility of understanding organizations and organizational practices in the field of Organizational Studies, Work and Society (EOS) in a perspective that will beyond productivism to consider the human factor. Cartography thus appears as a theoretical-methodological possibility as a form of production of a territory that is produced at the same time that the research itself is produced, in a rozomatic way. The cartographic tracking took the academic researcher to the Health Department of the City of Cachoeiro de Itapemirim/ES for a period of 25 days in which it was possible to experience different situations covered in the chapter: my days at SEMUS. In additional interviews were also carried out with three people (users of the mental health municipal service), the so-called beginning researchers, who actively participated in the corrections and analysis of their stories, in an autobiographical narrative. Subjections in the world of work are present in the narratives presented in the first person. The affective approach and music emerge as devices of agency the affections present in cartographic work: medicalization and courage; prejudice and faith; control and time.